Role of Оrientation of Рersonality in Аdaptation to Violations of Dynamics between an Organism and Environment - O. Miroshnychenko (Ukrainian Antarctic Journal, 2012)
In the article a question is examined about intercommunication between the social orientation of personality and by possibilities of adaptation to the changed terms of vital functions, the role of account is underlined socially meaningful qualities of personality in the selection of participants of arctic expeditions.